John Leguizamo [videorecording (DVD)] : tales from a ghetto klown - DeJesus, Ben; Leguizamo, John (PBS Home Video, 2012)
Actor, playwright and bi-cultural comedian, John Leguizamo shares stories from his rise to success and his struggles with his one-man Broadway show "Ghetto Klown."